A 3′ untranslated region polymorphism rs2304277 in the DNA repair pathway gene OGG1 is a novel risk modulator for urothelial bladder carcinoma. (15th November 2017) - Ahmed, Tayyaba; Nawaz, Saira; Noreen, Rabia; Bangash, Kashif Sardar; Rauf, Abdur; Younis, Muhammad; Anwar, Khursheed; Khawaja, Muhammad Athar; Azam, Maleeha; Qureshi, Abid Ali; Akhter, Saeed; Kiemeney, Lambertus A.; et al.
Summary: Altered DNA repair capacity may affect an individual's susceptibility to cancers due to compromised genomic integrity. This study was designed to elucidate the association of selected polymorphisms in DNA repair genes with urothelial bladder carcinoma (UBC). OGG1 rs1052133 and rs2304277, XRCC1 rs1799782 and rs25487, XRCC3 rs861539, XPC rs2228001, and XPD rs13181 were genotyped using polymerase chain reaction–restriction fragment length polymorphism (PCR‐RFLP) in 200 UBC cases and 200 controls. We found association of OGG1 rs2304277 [odds ratio (OR)GG = 3.55, 95% confidence interval (CI) = 1.79–7.06] and XPC rs2228001 (ORAC = 2.38, 95% CI = 1.43–3.94) with UBC. In stratified analysis with respect to smoking status, OGG1 rs2304277 and XPC rs2228001 exhibited increased risk in smokers [(rs2304277 ORGG = 4.96, 95% CI = 1.51–16.30) (rs2228001 ORAC = 2.19, 95% CI = 1.02–4.72)] as well as nonsmokers [(rs2304277 ORGG = 2.95, 95% CI = 1.26–6.90) (rs2228001 ORAC = 2.57, 95% CI = 1.31–5.04)]. These polymorphisms were also associated with both low‐grade [(rs2304277 ORGG = 3.73, 95% CI = 1.72–8.09) (rs2228001 ORAC = 2.18, 95% CI = 1.21–3.92)] and high‐grade tumors [(rs2304277 ORGG = 3.45, 95% CI = 1.52–7.80) (rs2228001 ORAC = 2.81, 95% CI = 1.48–5.33)] as well as with non–muscle‐invasive bladder cancer [(rs2304277 ORGG = 4.03, 95% CI = 1.87–8.67) (rs2228001 ORAC = 2.14, 95% CI = 1.20–3.81)] and muscle‐invasive bladder cancer [(rs2304277 ORGG = 3.06, 95%CI = 1.31–7.13) (rs2228001 ORAC = 2.95, 95%CI = 1.51–5.75)]. This is the first study on DNA repair gene polymorphisms and UBC in the Pakistani population. It identifies OGG1 rs2304277 and replicates XPC rs2228001 as significant modulators of UBC susceptibility.